Superconductivity in La1−xSmxO0.5F0.5BiS2 (x = 0.2, 0.8) under hydrostatic pressure. (14th June 2016) - Kalai Selvan, G; Thakur, Gohil S; Manikandan, K; Banerjee, A; Haque, Zeba; Gupta, L C; Ganguli, Ashok K; Arumugam, S
Abstract: We have investigated the pressure effect on the newly discovered samarium-doped La1− x Sm x O0.5 F0.5 BiS2 superconductors. More than a threefold increase in T c (10.3 K) is observed with external pressure (at 1.74 GPa at a rate of 4.08 K GPa −1 ) for x = 0.2 composition. There is a concomitant large improvement in the quality of the superconducting transition. Beyond this pressure T c decreases monotonously at the rate of −2.09 K GPa −1 . In the x = 0.8 sample, we do not observe any enhancement in T c with the application of pressure (up to 1.76 GPa). The semiconducting behavior observed in the normal-state resistivity of both samples is significantly subdued with the application of pressure which, if interpreted by invoking the thermal activation process, implies that the activation energy gap of the carriers is significantly reduced with pressure. We believe these observations should generate further interest in La1− x Sm x O0.5 F0.5 BiS2 superconductors.